Analisis Persentase Bagi Hasil Muzara’ah Pertanian Padi Dalam Upaya Peningkatan Pendapatan Masyarakat Penggarap Melalui Tinjauan Tiga Indikator Maqashid Syariah (Studi Kasus: Petani Padi Di Desa Klaten) - Ego Pasha, Aprielle; Apriel, Zuhra (Risalah Iqtishadiyah, 2023)
Indonesia is renowned as one of the largest rice producers in Asia, attributed to its fertile land conditions, encompassing 88.4%. This study aims to examine the profit-sharing percentage in Muzara'ah rice farming to enhance income for landowners and cultivators in the Klaten Regency. Employing a mixed-method approach, combining quantitative and qualitative methods, the research utilizes both primary and secondary data analyzed through Ordinary Least Square (OLS) methodology. Data collection involves questionnaires, documentation, and literature reviews with a sample size of 30 individuals. The study focuses on a population of 30 individuals utilizing a profit-sharing system under the Muzara'ah agreement in Klaten Regency. The Partial t-Test results indicate that the Muzara'ah Profit-Sharing Percentage significantly influences three Shariah Maqashid indicators positively. However, efforts to increase community income do not impact the three Shariah Maqashid indicators significantly. The F-Test suggests that some variables do not have a significant impact. Furthermore, the R2 Test reveals a value of 0.134, signifying that 13.4% of the Muzara'ah Profit-Sharing Percentage has the most substantial influence on the three Shariah Maqashid indicators, while the remaining 86.6% is attributed to other contributing variables.